Aplicación del método de pólya para el aprendizaje de funciones lineales y cuadráticas en los estudiantes de primer año de bachillerato general unificado del colegio de bachillerato Pío Jaramillo Alvarado de la cuidad de Loja, período 2015-2016. - Ramos Ramos, Mariuxi Cecibel (2017)
The present research aims to investigate the application of the Pólya method to improve the learning of linear and quadratic functions in first year students of Unified General Baccalaureate of the Pío Jaramillo Alvarado Baccalaureate of the city of Loja, period 2015-2016. The aim of the research process was to improve the learning of linear and quadratic functions by applying the Pólya Method. The research responded to a descriptive (diagnostic) and pre-experimental design. The phases that were used in their order were the following: comprehensive, diagnostic, modeling, application and evaluation of the effectiveness of linear and quadratic function learning, as verified by the Wilcoxon rank test, And mitigate the difficulties, deficiencies and needs present in learning. The research showed that students present difficulties in solving problems of linear and quadratic functions. In addition, the application of the Pòlya method allows students to develop the ability to solve problems of linear and quadratic functions, facilitating their learning. The main results obtained as a result of the research process are as follows: in the educational process the applied methodology does not allow students to internalize the content of linear and quadratic functions. However, by applying the Pólya method adequately serves to improve the learning of linear and quadratic functions in first year students of unified general baccalaureate.